Determinan Perilaku Sadari Remaja Putri Dalam Upaya Deteksi Dini Kanker Payudara - Shinta Deby Afianti; Sarah Handayani; Alibbirwin (UHAMKA Press, 2019)
ABSTRACT The prevalence of breast cancer continues to increase by 1.4 per 1,000 population and cause of death number 7 (5.7%) from all causes of death Since 2007-2013 early detection of breast cancer has been carried out by women as many as 644,951 people (1.75%) with the discovery of a lump suspect (tumor) 1682 people or 2.6 per population. Where as SADANIS (Clinical Breast Check) program showed an increase to (57%) to 1,623,913 people from 904,099 at the end of 2014. The purpose of this research is to know Factors related to SADARI Behaviour Young Woman in the early detection efforts of breast cancer in SMA Putra Bangsa Depok Year 2019. By using quantitative research using Cross Sectional design. The data used is primary data with angket filling. The analysis used is univariate analysis and bivariate. Total population of 93 students. Results of sufficient indicate there is a relationship between knowledge, exposure to information, support of parents, perception of seriousness and perception of barriers with SADARI Behaviour (p value < 0.05). Therefore recommended to include health counseling and health programs such as developing SADARI Poster and simulated practice aware to improve the youth's understanding of it. Keywords: Breast Cancer, SADARI, Adolescents, and Factors of SADARI.